Effects of Prolonged Exposure to Hypobaric Hypoxia on Oxidative Stress: Overwintering in Antarctic Concordia Station. (30th April 2022) - Mrakic-Sposta, Simona; Montorsi, Michela; Porcelli, Simone; Marzorati, Mauro; Healey, Beth; Dellanoce, Cinzia; Vezzoli, Alessandra
Abstract : Concordia Station is the permanent, research station on the Antarctic Plateau at 3230 m. During the eleventh winter-over campaign (DC11-2015; February 2015 to November 2015) at Antarctic Concordia Station, 13 healthy team members were studied and blood samples were collected at six different time points: baseline measurements (T0), performed at sea level before the departure, and during the campaign at 3, 7, 20, 90, and 300 days after arrival at Concordia Station. Reducing the partial pressure of O2 as barometric pressure falls, hypobaric hypoxia (HH) triggers several physiological adaptations. Among the others, increased oxidative stress and enhanced generation of reactive oxygen/nitrogen species (ROS/RNS), resulting in severe oxidative damage, were observed, which can share potential physiopathological mechanisms associated with many diseases. This study characterized the extent and time-course changes after acute and chronic HH exposure, elucidating possible fundamental mechanisms of adaptation. ROS, oxidative stress biomarkers, nitric oxide, and proinflammatory cytokines significantly increased (range 24-135%) during acute and chronic hypoxia exposure (peak 20 th day) with a decrease in antioxidant capacity (peak 90 th day: -52%). Results suggest that the adaptive response of oxidative stress balance to HH requires a relatively long time, more than 300 th days, as all the observed variables do not return to the preexposition level. These findings may also be relevant to patients in whom oxygen availability is limited through disease (i.e., chronic heart and lung and/or kidney disease) and/or during long-duration space missions.